2017
DOI: 10.1016/j.ymeth.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Precision genome editing using CRISPR-Cas9 and linear repair templates in C. elegans

Abstract: The ability to introduce targeted edits in the genome of model organisms is revolutionizing the field of genetics. State-of-the-art methods for precision genome editing use RNA-guided endonucleases to create double-strand breaks (DSBs) and DNA templates containing the edits to repair the DSBs. Following this strategy, we have developed a protocol to create precise edits in the C. elegans genome. The protocol takes advantage of two innovations to improve editing efficiency: direct injection of CRISPR-Cas9 ribon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
223
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(226 citation statements)
references
References 24 publications
1
223
0
2
Order By: Relevance
“…2A). To test this further, using genome editing (Paix et al, 2017), we 106 regenerated the meg-4 deletion in a line carrying the meg-3 deletion to generate three new meg-3 meg-107 4 lines (meg-3 meg-4 #2 , meg-3 meg-4 #3 , and meg-3 meg-4 #4 ). Strikingly, we found that the newly 108 generated meg-3 meg-4 lines remained competent for RNAi for at least five generations before 109 beginning to exhibit resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2A). To test this further, using genome editing (Paix et al, 2017), we 106 regenerated the meg-4 deletion in a line carrying the meg-3 deletion to generate three new meg-3 meg-107 4 lines (meg-3 meg-4 #2 , meg-3 meg-4 #3 , and meg-3 meg-4 #4 ). Strikingly, we found that the newly 108 generated meg-3 meg-4 lines remained competent for RNAi for at least five generations before 109 beginning to exhibit resistance.…”
mentioning
confidence: 99%
“…Results 86 meg-3 meg-4 mutants are defective in exogenous RNA-mediated interference 87 JH3475 is a strain in which both the meg-3 and meg-4 open reading frames have been deleted 88 by genome editing (Smith et al, 2016;Paix et al, 2017). This strain (meg-3 meg-4 #1 ) has been passaged 89 over 100 times.…”
mentioning
confidence: 99%
“…Null, tagged, and mutated versions of gcna-1 were created by CRISPR/Cas9 genome engineering. For null alleles ea43 and linked double mutant lines, 5' gcna-1 crRNA CTC GGG TGA AGC TAT CTA TAC TCA TGT AAT TTT TAT TAT GTA CTA CAC T. Injection mixes containing crRNA, tracrRNA, ssDNA ultramers, and Cas9 protein were prepared as described (Paix et al, 2017). crRNA and ssDNA repair template for dpy-10(cn64) co-injection marker were also included (Arribere et al, 2014).…”
Section: Generation Of C Elegans Crispr Allelesmentioning
confidence: 99%
“…This is in contrast to the HMEJ experiments described above [Yao et al 2017] where long homology arms perform better than short homology arms. A detailed protocol on performing edits of either DNA insertions or deletions using short homology arms has recently been published and contains useful tips [Paix et al 2017b]. …”
Section: Recent Advances For Site-specific Insertion Of Relatively Lamentioning
confidence: 99%